A Statistical Design Approach for an Effective Catalyst in the Fenton Reaction in Case of Fe3O4-MOF MIL-88b (Fe) in Methylene Blue Degradation Kinetics - Daniel, Saman; Bondarenko, L.S.; Baimuratova, R.K.; Dzeranov, A.A.; Dzhardimalieva, G.I.; Tropskaya, N.S.; Kydralieva, K.A. (Karagandy University of the name of acad. E.A. Buketov, 2024)
In this paper composites containing metal-organic framework MIL88b(Fe), nanoparticles magnetite (Fe3O4) or maghemite (γ-Fe2O3) modified by humic acids or ascorbic acid were synthesized and tested in the decomposition reaction of methylene blue. Analysis of predictive model based on multi-factor correlation analysis “physical-chemical properties — concentration of methylene blue after degradation” showed that in a line of selected parameters (initial iron concentration in sample, elemental cell parameter, Fe2+/Fe3+ ion ratio on sample surface, total iron ion released concentration, surface area specific, surface charge), a significant factor influencing Fenton reaction kinetics, is only the total concentration of the released iron ions (p-value = 0.0162). The influence of separate Fe2+ and Fe3+ ions and reaction time on the Fenton reaction kinetics was evaluated by multi-factor analysis. The results demonstrated that concentrations of released iron ions are statistically significant, with a square of the concentration of ions Fe2+ and the result of the reaction time to the concentration of ions Fe3+. A comparison of the sign and the coefficient values shows that an increase in ion concentration results in a reduction in methylene blue concentration, thereby accelerating the Fenton reaction rate, with Fe2+ ion concentration affecting more than Fe3+. The resulting model is proposed as a means of selecting a sample with the maximum Fenton reaction rate at a given point in time.
Keywords: Fenton reaction; MOFs; methylene blue; degradation kinetics; MIL-88b (Fe); heterogeneous catalysts; predictive model; multivariate correlation analysis